2022
DOI: 10.1155/2022/2644205
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Retardation Affects Intestinal Health of Suckling Piglets via Altering Intestinal Antioxidant Capacity, Glucose Uptake, Tight Junction, and Immune Responses

Abstract: The aim of the present study was to investigate the effects of intrauterine growth retardation (IUGR) on the intestinal morphology, intestinal epithelial cell apoptosis, intestinal antioxidant capacity, intestinal glucose absorption capacity, and intestinal barrier function of piglets during the suckling period. A total of eight normal-birth-weight (NBW) piglets and eight IUGR newborn piglets (Duroc × Landrace × Yorkshire) were selected from eight litters, one NBW and one IUGR newborn piglet per litter. In eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…The gut microbiota maintains a symbiotic relationship with the host and regulates several important functions including host metabolism, nutrients digestion and absorption, immunity, and intestinal barrier function (5,29). So, the dynamic balance of intestinal microbiota is crucial for animal intestinal health, while optimum intestinal health is crucial to animal growth and health (30,31). Growing shreds of evidence demonstrated that many factors including diets can affect the gut microbiota community and function (6,7,29,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota maintains a symbiotic relationship with the host and regulates several important functions including host metabolism, nutrients digestion and absorption, immunity, and intestinal barrier function (5,29). So, the dynamic balance of intestinal microbiota is crucial for animal intestinal health, while optimum intestinal health is crucial to animal growth and health (30,31). Growing shreds of evidence demonstrated that many factors including diets can affect the gut microbiota community and function (6,7,29,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the NOD-like receptor signaling pathway [ 67 ], tight junction [ 17 ] and MAPK signaling pathway [ 68 ] are related to the occurrence of IUGR.…”
Section: Discussionmentioning
confidence: 99%
“…The spleen is the largest body immune organ and contains both lymphocytes and macrophages, comprising a quarter of the lymphatic tissue [ 15 ]. Currently, there are not many researches about the IUGR, and the majority of studies on IUGR focus on certain tissues, such as the intestine [ 16 , 17 ], placenta [ 18 ], liver [ 19 , 20 ] and muscles [ 21 ], whereas studies referring to the spleen are relatively scarce. Spleen development is essential for establishing the acquired immunity of newborns.…”
Section: Introductionmentioning
confidence: 99%
“…IUGR usually refers to impaired growth and development of the embryo and/or its organs during pregnancy [ 1 , 2 ]. Pigs, a kind of multifetal mammal, exhibit a high incidence of IUGR, which seriously affects the postnatal growth and intestinal health of piglets and ultimately affects the economic benefit of pig production [ 3 , 4 ]. Studies have confirmed that piglets with IUGR are associated with feeding intolerance and intestinal dysfunction [ 4 , 5 ], which leads to a retard growth and poor health status of pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Pigs, a kind of multifetal mammal, exhibit a high incidence of IUGR, which seriously affects the postnatal growth and intestinal health of piglets and ultimately affects the economic benefit of pig production [ 3 , 4 ]. Studies have confirmed that piglets with IUGR are associated with feeding intolerance and intestinal dysfunction [ 4 , 5 ], which leads to a retard growth and poor health status of pigs. Therefore, strategies to alleviate intestinal injury and promote intestinal development may help to reverse the growth retardation in IUGR pigs.…”
Section: Introductionmentioning
confidence: 99%